HUBUNGAN BESAR UANG SAKU, PENDAPATAN ORANG TUA SERTA PENGETAHUAN LABEL GIZI TERHADAP PERILAKU MEMBACA LABEL GIZI DALAM PEMILIHAN JAJANAN KEMASAN DI SMAN 1 KOTA SERANG TAHUN 2020 - Siesqia Farah Nurfatin (2020)
Teenagers spend more time outside the home, so they often eat snacks. Snacks that consumed must be fit with the needs to fulfill the nutrients needed for growth and development and support their many activities. The amount of nutrients consumed can be determined through nutrition labels. This study aims to determine the relationship between pocket money, parent's income and knowledge of nutrition labels on the behavior of reading nutrition labels in the selection of snacks at SMAN 1 Serang City. This study uses a cross-sectional design by taking a sample with purposive sampling technique. The sample selected was 36 students aged 16-18 years. Data was collected and collected using a questionnaire. Relationship analysis was performed using the Pearson Chi-Square test. The analysis showed that the pocket money (p = 0.307), parent's income (p = 0.637), and nutrition label knowledge (p = 1,000) on the behavior of reading nutrition labels in the selection of snacks. This shows that there is no relationship between the amount of pocket money, parent's income, and knowledge of nutrition labels on the behavior of reading nutrition labels in the selection of snacks at SMAN 1 Serang City.